Effects of Five Plant Essential Oils on the Protein Content and Digestive Enzymes of Ephestia kuehniella - Mohammad Asadi (Tunisian Journal of Plant Protection, 2023)
Asadi, M. 2023. Effects of five plant essential oils on the protein content and digestive enzymes of Ephestia kuehniella. Tunisian Journal of Plant Protection 18 (1): 29-39.